Respuesta :
Answer:
(0, - [tex]\frac{4}{3}[/tex] )
Step-by-step explanation:
Given the 2 equations
3y = x - 4 → (1)
6x - 6y = 8 → (2)
Rearrange (1) expressing x in terms of y by adding 4 to both sides
x = 3y + 4 → (3)
Substitute x = 3y + 4 into (2)
6(3y + 4) - 6y = 8 ← distribute and simplify left side
18y + 24 - 6y = 8
12y + 24 = 8 ( subtract 24 from both sides )
12y = - 16 ( divide both sides by 12 )
y = [tex]\frac{-16}{12}[/tex] = - [tex]\frac{4}{3}[/tex]
Substitute y = - [tex]\frac{4}{3}[/tex] into (3) and solve for x
x = 3(- [tex]\frac{4}{3}[/tex] ) + 4 = - 4 + 4 = 0
Solution is (0, - [tex]\frac{4}{3}[/tex] )